Change in sagittal profile after implantation of anchored interbody cage in the surgical procedure for degenerative cervical spine disease - Opsenak, Rene; Hanko, Martin; Snopko, Pavol; Benco, Martin; Hanzel, Radoslav; Kolarovszki, Branislav (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2021)
BACKGROUND: The aim of this study was to verify the relationship between changes in the segmental sagittal profile (SSP) and changes in the global sagittal profile (GSP) after anterior cervical discectomy with anchored cage implantation (ACDF). STUDY DESIGN: Prospective study with 2-year follow-up. METHODS: This study includes 104 patients after 1-level or 2-level ACDF operated between the May 2013 and March 2016. SSP was evaluated by Cobb angle measurement of operated motion segment (CobbS) and GSP was evaluated by Cobb angle measurement in C2-C7 segments (CobbG). Both SSP and GSP were measured pre- and postoperatively within a 24 months follow-up period. The influence of factors such as age, gender, number of treated segments and osteoporosis was evaluated using t-tests. The correlation between SSP and GSP changes was assessed by Pearson's correlation coefficient. RESULTS: In the early postoperative period after 1-level ACDF, there was a significantly greater increase in CobbS compared to that of the 2-level ACDF (P=0.0149). Male patients experienced a significant decrease of CobbG during the first 6 months after surgery as well as patients with osteoporosis within 12 months after ACDF. After ACDF the SSP change weakly correlated with the GSP change. CONCLUSION: SSP change after 1- or 2-level ACDF correlates mostly weakly with GSP change. Male gender and osteoporosis were identified as risk factors for global lordotisation following ACDF.
Keywords: Osteoporosis; prospektivní studie; retrospektivní studie; Spinal Fusion; diskektomie; Cervical Vertebrae; Humans; lidé; risk factors; fúze páteře; Retrospective Studies; Diskectomy; sagittal profile; Treatment Outcome; anchored cage; anterior cervical discectomy; Prospective Studies; výsledek terapie; krční obratle; osteoporóza